Pembuatan Bedak Nampu dari bahan alami: proses, manfaat, dan potensi pengembangan - Rijal, Rijal; Marlyn, Melanie; Melda; Alfisyahwan, Fiqra Aidil; Arsyad, Muh. Ashari (Jurnal Dedikasi Masyarakat, 2021)
Bedak Nampu is a traditional skincare product made from natural ingredients such as rice, turmeric, and temulawak, which has been used for generations by the community in Salomallori Village, Dua Pitue District, Sidrap Regency. Despite its beneficial effects on skin health, its utilization remains limited to small-scale production using traditional methods that are less efficient. The community service program through the Kuliah Kerja Nyata (KKN) Posko 23 aims to enhance the quality and competitiveness of Bedak Nampu by implementing production innovations, standardizing ingredients, and adopting digital marketing strategies. The methods applied include observation, training, innovation implementation, packaging design, as well as evaluation and monitoring. The results indicate improvements in production efficiency, product quality enhancement, and increased market competitiveness through modern packaging and digital marketing. With the applied innovations, Bedak Nampu has the potential to develop into a leading MSME product that not only preserves cultural values but also enhances the economic well-being of the local community.